Arcade Architecture Naning City by Intervening in Public Art to Create a Sustainable Landscape Development Strategy: Arcade Architecture Naning City by Intervening in Public Art to Create a Sustainable Landscape Development Strategy - Lu, Chen; Sodbhiban, Pichai; K-so, Narinthra; Kaewsaisoon, Wanchai (RATANABUTH JOURNAL, 2024)
This study investigates the importance of integrating public art into the sustainable development of historical and cultural arcade areas in Nanning City, Guangxi Province. The study found that public art enhances cultural value and History of the area which will help in sustainable development by using public art intervention methods. To revive the region’s landscape, history and culture. Improve citizens’ orientation and knowledge of their identities towards these areas. which can effectively deal with the identity crisis prevalent in today’s urban landscape. And this study will create a systematic and collaborative intervention strategy through the analysis of practice cases. The study concluded that public art intervention It serves as a contemporary representation of the spiritual essence of the place. It plays an important role in enhancing the landscape of the historical and cultural arcade area in Nanning. and effective inheritance of culture in the region Achieve sustainable development in renewing the historical and cultural arcade region of Nanning City.